Relación de los niveles de Hemoglobina y hematocrito con el IMC, edad y sexo en niños menores de 9 años de edad del Centro Poblado el Trópico Distrito de Huanchaco, en Setiembre del 2016 - Portilla Guevara, Marco Antonio Junior (2017)
The objective was to determine the relationship of hemoglobin and hematocrit levels with BMI, age and sex in children under 9 years of age from the Centro Poblado el Tropico District of Huanchaco, in September, 2016. Material and Method: The study was descriptive , Cross-sectional and prospective. Participants included 65 children under the age of 09 of both sexes, with prior consent and informed consent before inclusion in the study. Anthropometric measurements were performed using the following variables: weight (Kg) and height (cm), determination of hemoglobin (Hb) by cyanometahemoglobin method and hematocrit (Hto) by microcentrifugation. The determinations were analyzed and compared with BMI, age and sex. RESULTS: The mean values in the children under age were Hb 11.33 ± 2.85 g / dl, hto 39.47 ± 10.49%, BMI 19.61 ± 9.06 and age 7.41 ± 6.29. 7.8% had decreased Hb values and BMI corresponded to low weight, 28.2% in girls and 45.3% in boys (x2 = 0.39, P> 0.05). 7.8% had decreased Hb values according to the age group, with 4.7% in the 0-3 year group, 1.6% in the 4-6 year group and 1.6% in the 7-9 year age group (x2 = 12476, P> 0.05). 7.8% presented decreased Hb values corresponding to 6.3% of males and 1.6% of females (x2 = 1.006, P> 0.05). 6.3% had Hto values decreased and BMI corresponded to low weight, 28.1% in girls and 45.3% in boys (x2 = 1,527, P> 0.05). 6.3% had Hto values decreased according to the age group, being 4.7% the group of 0-3 years and 1.6% between 4-6 years of age (x2 = 12,476; P> 0.05). 6.3% had decreased Hto values corresponding to 4.7% of males and 1.6% of females, (x2 = 1,866, P> 0.05). It is concluded that the highest percentage of children are found to have a low BMI due to possibly malnutrition and lack of protein in the diet, but with normal hemoglobin and hematocrit values